2016
DOI: 10.1186/s12967-016-1011-9
|View full text |Cite
|
Sign up to set email alerts
|

Micro-RNA-21 (biomarker) and global longitudinal strain (functional marker) in detection of myocardial fibrotic burden in severe aortic valve stenosis: a pilot study

Abstract: AimsMyocardial fibrosis (MF) is a deleterious consequence of aortic valve stenosis (AVS). Global longitudinal strain (GLS) is a novel left ventricular (LV) functional parameter potentially useful to non-invasively estimate MF. MicroRNAs (miRNAs) are non-coding small ribonucleic acids (RNA) modulating genes function, mainly through RNA degradation. miRNA-21 is a biomarker associated with MF in pressure overload. The aim of the present study was to find an integrated algorithm for detection of MF using a combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 44 publications
4
26
0
Order By: Relevance
“…miRNA21 is up-regulated in cardiomyocytes during the fibrotic process; indeed, both myocardial and circulating levels of miRNA21 are significantly higher in patients with AVS compared to controls, correlating with MG and fibrosis. Previous data from our group also showed how miRNA21 manifested both in interstitial tissueand myocytes, with the fibrous tissue representing the site of major expression 25 27 . In this study, miRNA21 levels are associated with an impaired myocardial deformation, evaluated by GLS, and a reduced SVi, together with altered diastolic function and increased non-invasively-estimated filling pressure.…”
Section: Discussionsupporting
confidence: 55%
“…miRNA21 is up-regulated in cardiomyocytes during the fibrotic process; indeed, both myocardial and circulating levels of miRNA21 are significantly higher in patients with AVS compared to controls, correlating with MG and fibrosis. Previous data from our group also showed how miRNA21 manifested both in interstitial tissueand myocytes, with the fibrous tissue representing the site of major expression 25 27 . In this study, miRNA21 levels are associated with an impaired myocardial deformation, evaluated by GLS, and a reduced SVi, together with altered diastolic function and increased non-invasively-estimated filling pressure.…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, this integrated approach could help in better stratifying those patients that currently fall in a diagnostic “gray zone” of AVS severity. [29]…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported the high accuracy of both native T1 relaxation time with a cut-off value ≥1,010 ms (Ss = 90%, Sp = 73%, AUC = 0.82) and ECV with a cut-off value ≥0.315 (Ss = 80%, Sp = 90%, AUC = 0.85) to identify extensive (> 30%) DMF at histology [24]. Moreover, correlations between both native T1 and ECV with prognostic markers such as NT-pro-BNP or troponin have been reported [28, 29]. CMR-T1 has therefore been proposed as a promising technique to identify early structural changes in patients with AS.…”
Section: Imaging Of Diffuse Myocardial Fibrosis In Asmentioning
confidence: 99%
“…First of all, GLS was found to be related to biomarkers of myocardial fibrosis such as those expressing calcification, collagen formation, or breakdown and inflammation [42, 43]. Several studies have also reported significant associations between LV systolic function and both FMF and DMF at CMR or myocardial histology [3, 14, 15, 18, 19, 24, 29, 44-46] (Table 2). Former studies have investigated the relationship between FMF and LV contractile function [14, 44, 45].…”
Section: Relationship Between Myocardial Fibrosis and LV Systolic Funmentioning
confidence: 99%